1998
DOI: 10.2334/josnusd.40.61
|View full text |Cite
|
Sign up to set email alerts
|

Retentive forces of two magnetic systems compared with two precision attachments.

Abstract: Magnetic retention devices based on cobalt/samarium alloy are new to dentistry, whereas precision attachments have been used for many years. In this study, the retentive forces of two magnetic systems were compared with two different precision attachment units. The retentive forces were evaluated with an Instron testing machine with a cross-head speed of 0.5 mm/min. Eight samples were used for each of the four attachments for a total of 32 samples. The attachments were embedded in an acrylic block and tested f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 10 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Some experiments [41,42] have shown deterioration of retentive force in other attachments by repeated insertion and detachment, but no loss in the retentive force of magnetic attachments. Conversely, Naert et al [43] and van Kampen [44] reported that the retention force of magnetic attachments was weak and deteriorated.…”
Section: Deterioration Of Retentive Forcementioning
confidence: 96%
“…Some experiments [41,42] have shown deterioration of retentive force in other attachments by repeated insertion and detachment, but no loss in the retentive force of magnetic attachments. Conversely, Naert et al [43] and van Kampen [44] reported that the retention force of magnetic attachments was weak and deteriorated.…”
Section: Deterioration Of Retentive Forcementioning
confidence: 96%
“…Figure 2 shows the iso-value curves of setting time with the changes in 4-META and filler contents, which was drawn using the Equation (2). As shown in Figs.…”
Section: Setting Time and Working Timementioning
confidence: 99%
“…As Rutkunas et al 1) reported, stud attachments are more susceptible to fatigue than magnets. Saygili and Sahmali 2) even reported that the retentive force of precision attachments decreased depending on the wear of female and male parts, while the magnetic retainers' retention increased over time and use according to the induction of magnetic fields. A dental magnetic attachment is usually composed of a magnet encapsulated in a cup yoke made of ferritic and austenitic stainless steels and a keeper made of ferritic stainless steel 3) .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic attachments for dentures are excellent retainers, however a keeper incorporated in a precious alloy root cap by casting or adhesion is susceptible to crevice or pitting corrosion and the cost of preparing the keeper in the root cap is not low [1][2][3][4][5][6][7] . Hirano et al have studied resin composites that can attract magnets and have written several valuable reports 2,8,9) .…”
Section: Introductionmentioning
confidence: 99%
“…UDMA/ MAA resin with an MAA mole fraction of 0.67 was used as the matrix resin. The effects of six levels of 4-META content (2,4,6,8,10, and 12 mass%) on the setting and flexural properties were studied. The metal filler content in each paste was 90 mass%.…”
mentioning
confidence: 99%